A clinical study on haemato-biochemical alterations in gastrointestinal disorders of dogs - Bhanu Pratap Singh; Pankaj Gupta; A.K Gupta; Hansraj Bhardwaj; Nawab Nashiruddullah; Vishal Kotwal (The Indian Veterinary Journal, 2024)
The study evaluated haemato-biochemical alterations and faecal examinations in 86 dogs, divided into three groups: healthy (n=12), gastroenteritis (n=61), and foreign body syndrome (n=13). Significant findings included lower Hb, PCV, TEC, Na, K, and Cl levels in both affected groups compared to healthy dogs. TLC, neutrophils, BUN, creatinine, TB, ALP, ALT, and AST were significantly elevated in the gastroenteritis group. Eosinophils were higher in foreign body syndrome. Parasitic eggs, particularly Toxocara spp. and Ancyclostoma spp., were prevalent in the foreign body group. These results aid in diagnostic and therapeutic decision-making for gastrointestinal disorders in dogs.